Safety and efficacy of digoxin: systematic review and meta-analysis of observational and controlled trial data. (30th August 2015) - Ziff, Oliver J; Lane, Deirdre A; Samra, Monica; Griffith, Michael; Kirchhof, Paulus; Lip, Gregory Y H; Steeds, Richard P; Townend, Jonathan; Kotecha, Dipak
Abstract : Objective To clarify the impact of digoxin on death and clinical outcomes across all observational and randomised controlled trials, accounting for study designs and methods. Data sources and study selection Comprehensive literature search of Medline, Embase, the Cochrane Library, reference lists, and ongoing studies according to a prospectively registered design (PROSPERO: CRD42014010783), including all studies published from 1960 to July 2014 that examined treatment with digoxin compared with control (placebo or no treatment). Data extraction and synthesis Unadjusted and adjusted data pooled according to study design, analysis method, and risk of bias. Main outcome measures Primary outcome (all cause mortality) and secondary outcomes (including admission to hospital) were meta-analysed with random effects modelling. Results 52 studies were systematically reviewed, comprising 621 845 patients. Digoxin users were 2.4 years older than control (weighted difference 95% confidence interval 1.3 to 3.6), with lower ejection fraction (33% v 42%), more diabetes, and greater use of diuretics and anti-arrhythmic drugs. Meta-analysis included 75 study analyses, with a combined total of 4 006 210 patient years of follow-up. Compared with control, the pooled risk ratio for death with digoxin was 1.76 in unadjusted analyses (1.57 to 1.97), 1.61 in adjusted analyses (1.31 to 1.97), 1.18 in propensity matched studies (1.09 to 1.26), and 0.99 in randomised controlled trials (0.93 to 1.05). Meta-regression confirmed that baseline differences between treatment groups had a significant impact on mortality associated with digoxin, including markers of heart failure severity such as use of diuretics (P=0.004). Studies with better methods and lower risk of bias were more likely to report a neutral association of digoxin with mortality (P<0.001). Across all study types, digoxin led to a small but significant reduction in all cause hospital admission (risk ratio 0.92, 0.89 to 0.95; P<0.001; n=29 525). Conclusions Digoxin is associated with a neutral effect on mortality in randomised trials and a lower rate of admissions to hospital across all study types. Regardless of statistical analysis, prescription biases limit the value of observational data.